Love in the afternoon - Kleypas, Lisa. (New York : St. Martin's Paperbacks, 2010)
Captain Christopher Phelan has been corresponding with the beautiful golden-haired Prudence Mercer while he was away fighting in the Crimean War. What he doesn't know, however, is that the woman who wrote to him is actually Prudence's best friend, Beatrix Hathaway. Upon his return home to Hampshire, it becomes clear that Christopher's experiences in war have changed him.
Series added by cataloger.
Keywords: Man-woman relationships -- Fiction; Crimean War, 1853-1856 -- Veterans -- Fiction; London (England) -- Social life and customs -- Fiction; Historical fiction; Love stories